Comparative Detectability of Planar Extended Defects of Sheet Metal by Reflection and Transmission Methods - Kirill S. Pavros; Irina G. Sidorenko; Bernd Rockstroh (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Currently, sheet metal is the main structural material for multi-purpose use. The actual task of the industry is to improve the quality of rolled sheet. It allows to ensure the necessary reliability of structures and products of especially critical use. The regulatory documents currently in force allow an ultrasonic testing of sheet metal by reflection or by transmission method. Due to lack of specific recommendations it becomes unclear which of the methods is preferable to use.Aim. An estimation of the maximum detectability of rolled sheet planar extended defects by reflection methods (echo method) and by transmission methods (shadow and mirror-shadow methods).Materials and methods. Based on analysis of the equations of acoustic paths, formulas were determined. The formulas allow one to evaluate an ultimate detectability of planar discontinuities of plate rolling by echo, shadow and mirror-shadow methods in a contact version by longitudinal waves. Experimental studies were conducted under computer simulation using the Mathcad mathematical package.Results. Integral expressions for calculating of amplitudes of echo signal from a plane defect, of bottom signal in defect-free and defective areas and their ratio for the echo method were obtained. The expressions for calculating of amplitudes of transmitted and bottom signals in defective and defect-free areas and their ratio for shadow and mirror-shadow methods were determined. Based on the numerical analysis, an estimation of the maximum detectability of planar extended defects of sheet metal was realized. It is possible to detect defects with a thickness of 5 pm by reflection methods and with a thickness more than 100 pm by transmission methods.Conclusion. It was established that reflection methods have better capabilities for detecting plane defects by longitudinal waves. The conditions for reducing of the thickness of the equivalent layer associated with an increase in transducers wave size were determined. It was shown that in order to detect defects with a small thickness, it is more expedient to give preference to the echo method of ultrasonic testing.